(untitled) (Perner’s Contacts, 2019)
The port of Hamburg is the largest German seaport lying on the banks of the Elbe River, 115 kilometres from its estuary into the North Sea. Within container transhipment, it is on the third rank among European ports beyond the Dutch port of Rotterdam, and the Belgium port of Antwerp. Hamburg belonged to the first European ports that started handling containers at the end of the 1960s. In 1990, the port handled 1.696 mil. TEUs, in 2017, it was already 8.815 mil. TEUs. The port of Hamburg has four container terminals, two of which are automated or semiautomated terminals. The terminals differ in technical equipment, transhipment technology, handling systems.